Analysis Of Service Performance, Customer Satisfaction On Customer Loyalty BRI Kangean - Sari, Winda (Dinamika: Jurnal Manajemen Sosial Ekonomi, 2022)
This study aims to determine the effect of service performance and customer satisfaction on customer loyalty at Bank BRI Kangean Unit. Sources in collecting data in this study through secondary data sources through literature studies from literature books, journals, the internet and articles that support the research. The data collection technique is through a questionnaire (questionnaire) to 38 respondents. The data processing test technique was carried out with validity and reliability tests, t tests and f test. The results of the study show that service performance has a positive and significant effect on customer loyalty, customer satisfaction has no significant effect on customer loyalty. Service performance and customer satisfaction together have no effect on customer loyalty. So in other words H1 is accepted, H2 is rejected and H3 is rejected. Quality Service performance at the Bank Bri Unit Kangean office is quite high but customer satisfaction is still low. Keywords: Service Performance, Customer Satisfaction, Customer Loyalty.